The Precambrian Khondalite Belt in the Daqingshan area, North China Craton: evidence for multiple metamorphic events in the Palaeoproterozoic era - Wan, Y.; Liu, D.; Dong, C.; Xu, Z.; Wang, Z.; Wilde, Simon; Yang, Y.; Liu, Z.; Zhou, H. (Geological Society Publishing House, 2009)
High-grade pelitic metasedimentary rocks (khondalites) are widely distributed in the northwestern part of the North China Craton and were named the ‘Khondalite Belt’. Prior to the application of zircon geochronology, a stratigraphic division of the supracrustal rocks into several groups was established using interpretative field geology. We report here SHRIMP U–Pb zircon ages and Hf-isotope data on metamorphosed sedimentary and magmatic rocks at Daqingshan, a typical area of the Khondalite Belt. The main conclusions are as follows: (1) The early Precambrian supracrustal rocks belong to three sequences: a 2.56–2.51 Ga supracrustal unit (the previous Sanggan ‘group’), a 2.51–2.45 Ga supracrustal unit (a portion of the previous upper Wulashan ‘group’) and a 2.0–1.95 Ga supracrustal unit (including the previous lower Wulashan ‘group’, a portion of original upper Wulashan ‘group’ and the original Meidaizhao ‘group’) the units thus do not represent a true stratigraphy; (2) Strong tectono-thermal events occurred during the late Neoarchaean to late Palaeoproterozoic, with four episodes recognized: 2.6–2.5, 2.45–2.37, 2.3–2.0 and 1.95–1.85 Ga, with the latest event being consistent with the assembly of the Palaeoproterozoic supercontinent Columbia; (3) During the late Neoarchaean to late Palaeoproterozoic (2.55–2.5, 2.37 and 2.06 Ga) juvenile, mantle-derived material was added to the crust.